Incomparability and practical reason - Chang, R; Chang, Ruth (1997)
﻿ In this thesis I aim to answer two questions: Are alternatives for choice ever incomparable? and, In what ways can items be compared? I argue that there is no incomparability among bearers of value and that the ways in which items can be compared are richer and more varied than commonly supposed. The two questions are closely related; in arguing against incomparability a positive picture of comparability emerges. The case against incomparability is a case for a new conception of comparability more capacious than has been traditionally conceived. This 'broad' conception of comparability has three distinctive features: it distinguishes incomparability from noncomparability, it includes the possibility of 'emphatic' comparability, or comparisons between 'higher' and 'lower' goods; and it makes logical space for a fourth generic value relation - what I shall call 'on a par' - beyond the standard trichotomy of relations of 'better than', 'worse than', and 'equally good'. Each of these features arises out of defects of certain incomparabilist arguments. Indeed, the approach to the broad conception of comparability via examination of incomparabilist arguments makes clear that much of the intuitive pull of incomparability depends on a narrow and impoverished conception of comparability. Investigation of comparability and incomparability is motivated by a proposed substantive account of practical justification according to which there can be no justified choice without the comparability of the alternatives. The existence of widespread incomparability, then, undermines the rationality of practical life. This thesis' argument against incomparability and for a broad conception of comparability serves to vindicate the role of practical reason in choice.